2015
DOI: 10.1016/j.colegn.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The rate and cost of nurse turnover in Australia

Abstract: Nurse turnover is a critical issue facing workforce planners across the globe, particularly in light of protracted and continuing workforce shortages. An ageing population coupled with the rise in complex and chronic diseases, have contributed to increased demands placed on the health system and importantly, nurses who themselves are ageing. Costs associated with nurse turnover are attracting more attention, however existing measurements of turnover show inconsistent findings which can be attributed to differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
138
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(147 citation statements)
references
References 19 publications
(16 reference statements)
2
138
0
7
Order By: Relevance
“…Turnover is a critical issue for the nursing workforce 1 , negatively affecting the health system regarding both disease prevention and the health and quality of the nursing services 2 . The shortage of nurses is a global problem 3 and the turnover of nurses is very high in comparison to other healthcare professions 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Turnover is a critical issue for the nursing workforce 1 , negatively affecting the health system regarding both disease prevention and the health and quality of the nursing services 2 . The shortage of nurses is a global problem 3 and the turnover of nurses is very high in comparison to other healthcare professions 4 .…”
Section: Introductionmentioning
confidence: 99%
“…43,44 Further, nursing turnover (when an employee leaves an organisation and is replaced) is expensive, both in direct costs associated with recruiting a replacement nurse, and in the indirect costs of lost productivity. 45,46 A national study of nursing turnover in Australia, conducted between 2008 and 2010, found that the cost of turnover in Australia was $49,255 per full-time medical/surgical nurse. 46 Other authors have suggested that turnover costs for specialist staff such as emergency nurses are even greater.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 A national study of nursing turnover in Australia, conducted between 2008 and 2010, found that the cost of turnover in Australia was $49,255 per full-time medical/surgical nurse. 46 Other authors have suggested that turnover costs for specialist staff such as emergency nurses are even greater. 47 By increasing nursing retention rates, organisations avoid the fiscal and human costs associated with recruitment, orientation and temporary labour coverage for vacant emergency nursing positions, and the quality of patient care delivery is improved.…”
Section: Discussionmentioning
confidence: 99%
“…While current estimates 1,2,12 indicate that the rural nursing workforce shortage is real, there is minimal evidence that explores the period after nurses resign and the impact of these rural nurse resignations on the nursing profession. Retaining experienced nurses will assist to alleviate the shortage and facilitate the transfer of knowledge and provision of quality care to patients.…”
Section: Introductionmentioning
confidence: 94%